Volumetric-gravimetric synergy in biomass-derived carbon supercapacitors: A case study on dried banana leaf waste - Apriwandi, Apriwandi (Universitas Riau, 2025)
Biomass-derived carbon-based supercapacitors are a compelling solution for environmentally friendly electrochemical energy storage, playing a crucial role in the transition to sustainable energy. Despite this potential, much of the existing research has overly concentrated on theoretical evaluations, hindering practical application. This study decisively addresses the performance of supercapacitors on both a volumetric and practical scale, underscoring their global applicability. The carbon material utilized in this research was expertly produced from dried banana leaf biomass, converted into solid carbon through a process of chemical activation with NaOH and high-temperature pyrolysis. The pyrolysis was carried out in an integrated fashion, combining carbonization and physical activation stages within a carbon dioxide (CO₂) gas atmosphere at temperatures of 700°C, 800°C, and 900°C. Initial characterization focused on density analysis to assess the structural integrity of the porous carbon electrodes. Electrochemical performance was rigorously evaluated using cyclic voltammetry (CV) for volumetric capacitance and galvanostatic charge-discharge (GCD) for gravimetric capacitance within a two-electrode system using a 1000 mmol/L Na2SO4 electrolyte. The results are compelling: the carbon material activated at 900°C achieved an exceptional volumetric capacitance of 198 F/cm³ and a gravimetric capacitance of 181 F/g. These results clearly demonstrate that banana leaf-derived activated carbon is not only viable but also a highly promising electrode material for supercapacitors, paving the way for practical applications in the field.